1999
DOI: 10.1159/000018066
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Pustular Psoriasis of Pregnancy (Impetigo herpetiformis)

Abstract: A 17-year-old woman had a sudden eruption of pustules in her intertriginous areas as well as of erythematosquamous plaques on the scalp, elbows, palms and soles in the third trimester of her first pregnancy. Histopathological evaluation of a biopsy revealed typical changes of pustular psoriasis with parakeratosis and abscesses of neutrophils (Kogoj’s spongiform pustules). The diagnosis of pustular psoriasis was established by the typical clinical and histopathological findings. Laboratory parameters showed a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 9 publications
0
48
0
4
Order By: Relevance
“…In corticosteroidunresponsive severe cases, cyclosporine has been used successfully to treat IH (11). Case reports have demonstrated successful treatment of postpartum IH with oral retinoids (12) or psoralen plus ultraviolet light A (PUVA) (13). Recalcitrant IH has been treated postpartum with a combination of PUVA and clofazimine or methotrexate.…”
Section: Discussionmentioning
confidence: 99%
“…In corticosteroidunresponsive severe cases, cyclosporine has been used successfully to treat IH (11). Case reports have demonstrated successful treatment of postpartum IH with oral retinoids (12) or psoralen plus ultraviolet light A (PUVA) (13). Recalcitrant IH has been treated postpartum with a combination of PUVA and clofazimine or methotrexate.…”
Section: Discussionmentioning
confidence: 99%
“…Although its absolute safety is difficult to prove, Puig et al [13] reviewed pregnancy outcomes of 219 cases who had been exposed to tumor necrosis factor antagonists and concluded that women who conceived while taking infliximab or other anti-tumor-necrosis-factor-α agents can be reassured regarding the continuation of pregnancy. Other studies have reported the successful treatment of persistent IH lesions using methotrexate or retinoid photochemotherapy [14,15]. However, the critical days for isotretinoin-induced defects appear to be any time between 15 and 40 days after conception, with most studies indicating that of the pregnancies that reach 20 weeks gestation, 25–30% will show malformation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Günümüzde, İH'nin gebeliğin spesifik bir dermatozu mu yoksa jeneralize püstüler psoriazisin bir formu mu olduğuna dair tartışmalar devam etmektedir. Birçok yazar, İH'nin püstüler psoriazisin gebelikte endokrin değişikliklerle alevlenen jeneralize formu olduğunu ileri sürmektedir 2 . Bazı yazarlar ise; İH'de hipokalsemi olması ve gebelikte gözlenmesi sebebiyle psoriazisten farklı bir hastalık olarak yorumlamışlardır 3,4 .…”
Section: Gi Riflunclassified